What's up in the ALPS. (December 2017) - Rieux-Laucat, Frédéric
Highlights: The ALPS is caused by defective lymphocyte apoptosis related to FAS or FASL defects. FAS haploinsufficiency is associated with partial clinical penetrance. Haploinsufficiency combined with somatic mutations are found in ALPS-FAS patients. DNTs and hyper Igs distinguish the ALPS-FAS from CTLA-4 related defects. Lymphocyte expansion in ALPS-FAS can be controlled by mTOR inhibitors. Abstract : The autoimmune lymphoproliferative syndrome (ALPS) is a non-malignant and non-infectious uncontrolled proliferation of lymphocytes accompanied by autoimmune cytopenia. This clinical entity was recognized in the mid 60s and its genetic etiology was described in 1995 by the discovery of the FAS gene mutations. This was the first description of a monogenic cause of autoimmunity but its non-Mendelian expression remained elusive until the description of somatic and germline mutations in ALPS patients. The related apoptosis defect accounts for the accumulation of autoreactive lymphocytes as well as for specific clinical and biological features that distinguish the ALPS-FAS from other monogenic causes of ALPS such as somatic mutations of RAS or the recently described CTLA-4 insufficiency. The recognition of these genetic diseases brought new information on the regulation of the adaptive immune responses and uncovered new therapeutical targets. Finally, the deciphering the role of somatic mutations may pave the way to the understanding of more common autoimmune diseases.